2021
DOI: 10.1055/s-0041-1729457
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the Multiple Layers Application and the Heating of Silane on the Bond Strength between Lithium Disilicate Ceramics and Resinous Cement

Abstract: Objective The study aimed to evaluate the bond strength between lithium disilicate ceramic and resinous cement when silane (Prosil, FGM) was applied in different amounts of layers under heating or not. Materials and Methods Sixty IPS E-max CAD ceramic (Ivoclar) was used. They were conditioned with 10% hydrofluoric acid for 20 seconds. The samples were distributed in six groups (n = 10): 1Sil, 1 layer of silane without heating; 1SilAq, 1 layer of silane with heating; 2Sil, 2 layers without heating; 2SilAq, 2 la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…20 The adhesive resin could infiltrate within the surface roughness and reinforce To use a silane agent enhances the wettability of the repaired surface by encouraging chemical bonding between the silica or glass fillers and the resin matrix material, according to several studies. 12,13,[22][23][24][25] Staxrud and Dahl 26 reported that the repair of resin composites with a universal adhesive proved as successful as a pure silane prior to the use of an adhesive agent. Moreover, Fornazari et al 27 found that the application of a universal bond containing silane eliminates the requirement for a separate use of silane coupling agent in the clinical procedure for aged resin composite repair.…”
Section: Discussionmentioning
confidence: 99%
“…20 The adhesive resin could infiltrate within the surface roughness and reinforce To use a silane agent enhances the wettability of the repaired surface by encouraging chemical bonding between the silica or glass fillers and the resin matrix material, according to several studies. 12,13,[22][23][24][25] Staxrud and Dahl 26 reported that the repair of resin composites with a universal adhesive proved as successful as a pure silane prior to the use of an adhesive agent. Moreover, Fornazari et al 27 found that the application of a universal bond containing silane eliminates the requirement for a separate use of silane coupling agent in the clinical procedure for aged resin composite repair.…”
Section: Discussionmentioning
confidence: 99%
“…The Cleaned restoration was then placed in an ultrasonic cleaner filled with distilled water for 4 min [ 26 ]. Then it was silanated (Calibra silane) and heated using a furnace for 1 min [ 28 ], and universal adhesive was applied (One coat7) according to the manufacturer’s instructions as previously described.…”
Section: Methodsmentioning
confidence: 99%
“…Silane (Relyx Ceramic Primer, 3M, St Paul, MN, USA) was applied to the internal surfaces of the lithium disilicate crowns for sixty seconds, then air dried. The second silane layer maximised the surface coverage and siloxane linkages without affecting bond strength 25 …”
Section: Methodsmentioning
confidence: 99%
“…The second silane layer maximised the surface coverage and siloxane linkages without affecting bond strength. 25 Crowns were luted to Ti-base abutments with an autocure resin cement (Multilink Hybrid Abutment Cement; Ivoclar Vivadent). During setting, the Ti-base abutments were affixed to the laboratory analogs and the screw access chamber and screw head protected with PTFE (polytetrafluoroethylene) tape (Isotape; TDV, Santa Catarina, Brazil) which was subsequently removed.…”
Section: Component Constructionmentioning
confidence: 99%